2018
DOI: 10.1038/s41598-017-19137-5
|View full text |Cite|
|
Sign up to set email alerts
|

Lithium chloride effectively kills the honey bee parasite Varroa destructor by a systemic mode of action

Abstract: Honey bees are increasingly important in the pollination of crops and wild plants. Recent reports of the weakening and periodical high losses of managed honey bee colonies have alarmed beekeeper, farmers and scientists. Infestations with the ectoparasitic mite Varroa destructor in combination with its associated viruses have been identified as a crucial driver of these health problems. Although yearly treatments are required to prevent collapses of honey bee colonies, the number of effective acaricides is smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 44 publications
2
69
1
Order By: Relevance
“…Recently, in scientifi c circles, an idea was pushed forward that various lithium compounds may be used in Varroa control. Research carried out by Ziegelmann et al [98] suggests that lithium salts may produce a marked acaricide effect. Our recent research proved the effi cacy of lithium-salt-based supplements ( Figure 6A), especially those containing lithium citrate in various concentrations.…”
Section: Infestation With Varroa Destructor and Mixed Virus Infectionsmentioning
confidence: 99%
“…Recently, in scientifi c circles, an idea was pushed forward that various lithium compounds may be used in Varroa control. Research carried out by Ziegelmann et al [98] suggests that lithium salts may produce a marked acaricide effect. Our recent research proved the effi cacy of lithium-salt-based supplements ( Figure 6A), especially those containing lithium citrate in various concentrations.…”
Section: Infestation With Varroa Destructor and Mixed Virus Infectionsmentioning
confidence: 99%
“…Alongside novel RNAi-based approaches [9], it was observed that lithium salts may offer promising and easy-to-use chemicals for effectively treating Varroa infestation. Furthermore, treatments have been published where 100% mite mortality was found in the brood-free period with minor or no mortality of adult bees, with certain concentrations of lithium-containing chemicals [10,11]. Lithium chloride has been described as a varroicide that acts in a systemic mode of action in a wide range of concentrations [10].…”
Section: Introductionmentioning
confidence: 99%
“…To be successful, control of V. destructor should be complex, involving biotechnological methods, as well as the use of both ‘hard’ (organophosphate coumaphos, pyrethroids tau ‐fluvalinate and flumethrin, or formamidine amitraz) and ‘soft’ (formic acid, oxalic acid, essential oils, or lithium chloride) acaricides . However, very few ‘hard’ acaricides are suitable for use in bee colonies since most are also toxic to the bees .…”
Section: Introductionmentioning
confidence: 99%